IDENTIFICATION OF BEST PRACTICES FOR PRINCIPALS WITH HIGHLY ACHIEVEMENT IN INDONESIA - Abdul Wahab Syakhrani; Nurul Aini; Rezki Akbar Norrahman; Thea Karuni Respati; Ignatius Septo Pramesworo (Indonesian Journal of Education (INJOE), 2023)
This qualitative research study aimed to identify the best practices for principals with achievements in Indonesia. The study was conducted using a qualitative approach, specifically through interviews with ten high-performing principals from different regions in Indonesia. The interviews were transcribed and analyzed using thematic analysis to identify common themes and patterns related to best practices. The findings of this study revealed that the best practices for principals with achievements in Indonesia were categorized into three main themes: instructional leadership, school climate and culture, and professional development. Instructional leadership involves setting high expectations for student achievement, providing adequate instructional support to teachers, and monitoring and evaluating student progress. School climate and culture focused on creating a positive and supportive school environment, promoting a sense of belonging, safety, and respect among all school community members. Professional development emphasizes continuous learning and growth for teachers and school leaders, supporting and investing in professional learning communities, providing access to high-quality resources and training, and creating a culture of innovation and risk-taking. The study also identified some unique practices specific to the Indonesian context, such as involving community stakeholders in decision-making processes, building strong relationships with local government officials, and promoting local culture and traditions in the school environment. The study highlights the importance of best practices in school leadership for improving school performance and outcomes in Indonesia. This study's findings can inform the development of policies and programs to improve school leadership practices and support high-performing principals in Indonesia. Further research is needed to explore the effectiveness of these practices in improving student achievement and well-being in the Indonesian context